PRAKTIK GADAI TANAH PERTANIAN DI NAGORI BANDAR RAKYAT, KECAMATAN BANDAR, KABUPATEN SIMALUNGUN - Leo Kusuma; Pani Akhiruddin Siregar; Kadri Bancin (Universitas Islam Negeri Sumatera Utara, 2020)
The research aims to see the practice of agricultural land pawn in Nagori Bandar Rakyat, Kecamatan Bandar, Kabupaten Simalungun. Methods of research with qualitative approach to phenomenology. The truth of phenomenology is fulfilled while the involvement of researchers as human instruments in the business can uncover, capturing the passion of the subject of economic phenomena or behavior in the field. Data obtained by interviews from the people Nagori Bandar Rakyat, Kecamatan Bandar, Kabupaten Simalungun who practiced the practice of agricultural land pawn. The results of the research showed the practice of agricultural land pawn in people Nagori Bandar Rakyat, Kecamatan Bandar, Kabupaten Simalungun not in accordance with sharia principles because of the detriment of either party. Because, the contract is done only to find profit. By giving a certain amount of money, murtahin got two advantages. Profit from the utilization of agricultural land guarantee and the debt from rahin. This happens because the public doesn‘t understand the Islamic Law well. The lack of Islam, even if the community does not know the impact, so that people do practice of agricultural land pawn according to customs.